Genome-wide identification and expression analysis of the GRAS family under low-temperature stress in bananas - Tong, Ning; Li, Dan; Zhang, Shuting; Tang, Mengjie; Chen, Yukun; Zhang, Zihao; Huang, Yuji; Lin, Yuling; Cheng, Zhenguang; Lai, Zhongxiong (Frontiers in Plant Science, 2023)
GRAS is a class of plant-specific transcription factors with important roles in growth and development, signal transduction and other processes in a variety of plants. To understand the biological functions of the GRAS gene family in banana, genome-wide identification and bioinformatics analysis of the banana GRAS gene family based on information from the banana M. acuminata, M. balbisiana and M. itinerans genomic databases, and some MaGRAS gene family members were examined for their tissue organ expression and response patterns to low temperature stress. The results showed that there were 73, 59 and 58 members of the MaGRAS, MbGRAS and MiGRAS gene families, respectively, and 56 genes were homologous genes in all three banana genomes. Phylogenetic analysis showed that GRAS can be divided into 12 subfamilies and genetic structure analysis showed that most bananas GRAS gDNA have no introns. The C-terminus of banana GRAS proteins is highly conserved and all contain intact GRAS structural domains. Banana GRAS gene promoters contained a large number of cis-elements related to growth and development, hormone and stress in adversity. The miRNA-MaGRAS targeting prediction results showed that seven MaGRAS genes were fully complementary paired with miR171 members. The expression of all seven genes was lowest in roots and five genes were highest in leaves during low-temperature stress; the expression of MaSCL27-2, MaSCL27-3 and MaSCL6-1 was significantly lower than the control, except for MaSCL27-2 which was slightly higher than the 28°C control at 4 h and dropped to the lowest at 24 h, 12 h and 4 h, respectively; the MaSCL27-4 and MaSCL6-2 expression was intermittently upregulated, rising to the highest expression at 24h, while the expression of MaSCL22 was less variable, remaining at the control level with small changes. The study of the tissue specificity of some MaGRAS members with targeting relationship with miR171 and their response patterns to low temperature stress provides excellent candidate reference genes and theoretical basis for further functional studies to resolve the banana GRAS family genes.